2012
DOI: 10.1088/0953-4075/45/18/185201
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of Be-like N3 +and Ne6 +ions: features of Be isoelectronic sequences ofZ⩽ 10

Abstract: Using a noniterative eigenchannel R-matrix method, we have studied the photoionization for ground 1S and excited 3, 1P initial states of the Be-like N3 + and Ne6 + ions, up to the energy range of the final photo-ionic 3d state. The autoionizing resonance structures arising from the ground and excited states are identified and characterized. Our calculated photoionization cross sections with excellent agreement between length and velocity gauges are compared with the available experimental and previous theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…• and 2pnd 1 P • Rydberg series of O 4+ (n = 6-10) [22], F 5+ (n = 6-10) [21] and Ne 6+ (n = 7-9) ions [23]. In this paper, we intend to present accurate resonance energies and widths of the 2pns 1 P…”
Section: Introductionmentioning
confidence: 99%
“…• and 2pnd 1 P • Rydberg series of O 4+ (n = 6-10) [22], F 5+ (n = 6-10) [21] and Ne 6+ (n = 7-9) ions [23]. In this paper, we intend to present accurate resonance energies and widths of the 2pns 1 P…”
Section: Introductionmentioning
confidence: 99%
“…To understand the evolution of resonances according to the nuclear charge, further calculations for photo ionization cross section of Mg-isoelectronic phosphorus(P) and analysis of resonance structures for the Mg-isoelectronic sequences, comparing our results for the Be-like sequences [49], will be performed.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] These studies have shown that, except for the resonances converging to the C 3+ 2p threshold, all the resonance series are perturbed by overlapping series converging to other thresholds. The beryllium isoelectronic sequence of ions is particularly interesting because of the effect of electron correlation effects due to the presence of near-degenerate doubly excited configurations in the ground configuration.…”
Section: +mentioning
confidence: 98%